The changing circumstance of atrial fibrillation ‐ progress towards precision medicine. (30th March 2016) - Camm, A. J.; Savelieva, I.; Potpara, T.; Hindriks, G.; Pison, L.; Blömstrom‐Lundqvist, C.
Abstract: The prevalence of atrial fibrillation (AF) in the general population is between 1% and 2% in the developed world and is higher in men than in women. The arrhythmia occurs much more commonly in the elderly, and the estimated lifetime risk of developing AF is one in four for men and women aged 40 years and above. Projected data from multiple population‐based studies in the USA and Europe predict a two‐ to threefold increase in the number of AF patients by 2060. The high lifetime risk of AF and increased longevity underscore the important public health burden posed by this arrhythmia worldwide. AF has multiple aetiologies and a broad variety of presentations. The primary pathologies underlying or promoting the occurrence of AF vary more than for any other cardiac arrhythmia, ranging from autonomic imbalance to organic heart disease and metabolic disorders, such as diabetes mellitus, metabolic syndrome, hyperthyroidism and kidney disease, and lifestyle factors such as smoking, alcohol consumption and participation in endurance sports. Biomarkers are increasingly being investigated and, together with clinical and genetic factors, will eventually lead to a clinically valuable detailed classification of AF which will also incorporate pathophysiological determinants and mechanisms of the arrhythmia. In turn, this will allow the development and application of precision medicine to this troublesome arrhythmia. Abstract : Content List – Read more articles from the symposium: Atrial fibrillation ‐ from atrial extrasystoles to atrial cardiomyopathy. What have we learned from basic science and interventional procedures